Reproductive behavior of Tropidurus spinulosus (Squamata: Tropiduridae) in captivity - Pelegrin, Nicolas (2019)
Tropidurus spinulosus (Cope, 1862) is a medium-sized lizard distributed in north-central Argentina, Paraguay, Bolivia, and Brazil (Carvalho 2013) that inhabits both rocky and forest habitats (Martori and Aún 1994, Cruz 1998). Although some facets of the lizard’s natural history, such as diet, reproduction, activity, thermal ecology, and habitat use have been studied (e.g., Perez et al. 1991, Vitt 1991, Colli et al. 1992, Martori and Aún 1994, Cruz et al. 1997, Cruz 1998, López-Juri et al. 2017), little is known about the reproductive behavior of the species. The behaviors associated with courtship and mating in captivity, including information on copulation length.